INVESTMENT COMMUNITY, LOVE OF MONEY, AND DEMOGRAPHIC FACTOR ON THE INTEREST OF INVESTING IN CAPITAL MARKET OF GEN Z IN WEST KALIMANTAN - Pheterson Davit Vernando; Syahbandi Syahbandi; Helma Malini; Giriati Giriati; Pramana Saputra (Jurnal Ekonomi, 2023)
Currently, there is a significant demand from Gen Z for specialized learning from social media influencers, especially in the field of investment. These investment classes indirectly form communities within them. Besides the existence of communities, Gen Z individuals must also instil the concept of a love for money within themselves. Due to their young age, Gen Z individuals find it challenging to set aside their money. However, a substantial amount of capital is not necessary for investment purposes, especially in the capital market. This research aims to determine how investment communities, the love of money, and financial literacy influence on the investment interest in the Capital Market of Gen Z in West Kalimantan. The addition of the minimum investment capital variable as a mediating variable is to understand its influence on the three independent variables. The research used the Likert Scale to assess perceptions, views, and attitudes through questionnaires. The results from 209 respondents indicate that investment communities and demographic factors positively and significantly influence investment interest. The love of money variable shows non-significant results on investment interest. The mediating variable of minimum investment capital indicates that it does not directly affect the three independent variables.